Implementation of Regional Regulation No. 12 of 2006 Concerning Boundary Line (Case Study of Boundary Line Violations in Tangerang Regency) - Dafina Putri Rahmawati; Wahyu Beny Mukti Setiyawan (Transpublika Publisher, 2025)
This research examines the implementation of Regional Regulation No. 12 of 2006 concerning Building Boundary lines in Tangerang Regency, as well as factors influencing violations of these regulations. The method used is a case study with a qualitative approach through field data collection. The results show that the implementation of the regional regulation has not been optimal due to various obstacles in supervision, socialization, and rule enforcement. Additionally, social and administrative factors also contribute to the high number of violations. This research provides an overview of the challenges faced in implementing boundary line regulations and serves as an important reference for local governments to improve policies and supervision mechanisms to increase community compliance. It is hoped that the results of this study can serve as a basis for formulating more effective strategies in enforcing boundary line regulations in the future.